Yellowknife, NT -- photograph ... - Seale, Linda N. (University of Alberta Library, 2011)
View west from Pilots' Monument in Old Town, Yellowknife, NT, to the new town area, high rises and Yellowknife Bay. The tower to the left with a red top is the Con Mine tower or Robertson Headframe at the disused Cominco gold mine (demolished October 29 2016). The tower was a prominent landmark for hikers and boaters, and was visible from aircraft landing in Yellowknife. The road is Franklin Avenue. Photograph taken January 2011: description updated October 2016 ...